Literature Review: VO2Max In Active Smokers (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Maximal aerobic capacity or maximal oxygen uptake (VO₂Max) is a key indicator of the capacity of the cardiovascular and respiratory systems to deliver oxygen to body tissues during intense physical activity. Smoking is known to negatively impact lung function and oxygen circulation, leading to a decrease in VO₂Max. This study aims to systematically review the results of previous studies on the effect of smoking on VO₂Max in active smokers. The method used is a descriptive literature study by analyzing various national and international scientific articles published between 2010 and 2024. The results show that active smokers have significantly lower VO₂Max values ​​than non-smokers. Chemicals in cigarettes such as nicotine and carbon monoxide cause a decrease in oxygen-binding capacity in the blood, impaired pulmonary ventilation, and decreased cardiac efficiency. The higher the frequency and duration of smoking, the greater the decrease in aerobic capacity. In conclusion, smoking directly contributes to a decrease in VO₂Max, thus negatively impacting an individual's physical fitness and physical performance.